2017
DOI: 10.1590/1806-93042017000100004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors for early interruption of exclusive breastfeeding: meta-analysis on Brazilian epidemiological studies

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
3
22
2
12
Order By: Relevance
“…A meta-analysis found that the mean prevalence of exclusive breastfeeding of children at six months of age in Brazil was only 25.0% (95% CI: 18.05 -31.96), which is considered low in relation to other countries. It should be noted that the study does not present specific data about preterm newborns, and yet low birth weight increased by 1.17 the chance (95% CI: 1.06 -1.29) of early interruption of exclusive maternal breastfeeding (17) .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A meta-analysis found that the mean prevalence of exclusive breastfeeding of children at six months of age in Brazil was only 25.0% (95% CI: 18.05 -31.96), which is considered low in relation to other countries. It should be noted that the study does not present specific data about preterm newborns, and yet low birth weight increased by 1.17 the chance (95% CI: 1.06 -1.29) of early interruption of exclusive maternal breastfeeding (17) .…”
Section: Discussionmentioning
confidence: 90%
“…The population consisted of all mothers and their preterm infants who were discharged from the neonatal unit from June to October 2015 and who attended the follow-up clinic in the first 15 days after discharge. The convenience sample consisted of a total of 21 preterm infants (four twins) and their mothers (17), selected according to the inclusion and exclusion criteria described below and who accepted to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent meta-analysis from national studies on the factors associated with early weaning, the authors observed that schooling plays a relevant role and may be associated with a higher maternal capacity to solve breastfeeding problems and discomforts, as well as greater assimilation of the breast milk benefits. 27 It should be noted in the present study that a family income lower or equal to one minimum wage was a protective factor against the EBF early interruption. Previous studies reported different associations, where lower family income was a risk factor for the breastfeeding early interruption.…”
Section: Variables N %mentioning
confidence: 45%
“…A melhor maneira de tratar estas alterações é efetuando a raspagem e alisamento corono-radicular, com auxílio de curetas, foices e equipamentos ultrassônicos. Essa é considerada a terapia de escolha, pois desorganiza o biofilme dental e diminui a quantidade de microrganismos periodontopatogênicos, como também auxilia no restabelecimento dos fatores que são considerados de saúde, como a coloração, textura gengival com aspecto de casca de laranja, ausência de sangramento e aparência gengival resiliente e firme (Santos et al, 2017).…”
Section: Introductionunclassified
“…, mães mais jovens e mães que retornam ao trabalho mais cedo no período pós-parto, favorecem o DP(PEREIRA-SANTOS et al, 2017). Cabe salientar que crianças que tiveram o AME interrompido precocemente, precisarão satisfazer sua necessidade fisiológica de sucção de outras formas, por esse motivo,…”
unclassified